2013
DOI: 10.3109/07435800.2012.745870
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Early Intensive Insulin Therapy on Body Fat Distribution andβ-Cell Function in Newly Diagnosed Type 2 Diabetes

Abstract: Objectives. The aim of this study was to evaluate the effects of early intensive insulin therapy on body fat distribution, lean body mass and β-cell function in patients with newly diagnosed type 2 diabetes. Methods. Thirty-eight subjects with newly diagnosed type 2 diabetes participated in a 12-week course of intensive insulin therapy. Patients were administered a 75 g oral glucose tolerance test (OGTT), underwent measurement of visceral and subcutaneous adipose tissues (VAT and SAT) using computed tomography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
6
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 34 publications
4
6
1
Order By: Relevance
“…In accordance with our data, increased levels of lean body mass have been shown after insulin therapy in type 2 diabetes subjects. 31,32 Our observation that insulin therapy resulted in elevated levels of SAT in HF/HS-STZ rats also agrees with data from some human studies. 32,33 However, three other clinical studies observed no change in SAT after insulin therapy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In accordance with our data, increased levels of lean body mass have been shown after insulin therapy in type 2 diabetes subjects. 31,32 Our observation that insulin therapy resulted in elevated levels of SAT in HF/HS-STZ rats also agrees with data from some human studies. 32,33 However, three other clinical studies observed no change in SAT after insulin therapy.…”
Section: Discussionsupporting
confidence: 91%
“…31,32 Our observation that insulin therapy resulted in elevated levels of SAT in HF/HS-STZ rats also agrees with data from some human studies. 32,33 However, three other clinical studies observed no change in SAT after insulin therapy. 10,31,34 We observed an insulin-induced increase in VAT, which likewise has been reported in human studies.…”
Section: Discussionsupporting
confidence: 91%
“…It is believed that EIT improves multiple adverse metabolic consequences by rapidly overcoming “glucolipotoxicity” in β-cells and other insulin target cells; especially liver and muscle, thereby reducing endogenous insulin requirements, facilitating “β-cell rest”, protecting β-cell function, and by improving insulin sensitivity [ 6 , 7 ]. Insulin also possesses anti-inflammatory and antioxidant properties that may help protect against endothelial dysfunction and vascular complications [ 8 11 ], positively altering the course of vascular disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…One study has suggested that decreases in tumour necrosis factor‐alpha may contribute to the positive effect of STII therapy on beta‐cells . Another study has provided evidence that decreased visceral fat and increased skeletal muscle mass following insulin treatment may be associated with the observed improvements in function . The liver is central to the pathogenesis of type 2 diabetes, with hepatic glucose production being tightly regulated by portal‐insulin concentration .…”
Section: Unanswered Questions and Challengesmentioning
confidence: 99%